1991
DOI: 10.1002/oms.1210261020
|View full text |Cite
|
Sign up to set email alerts
|

[CH2OH+, C2H4] and [C2H5+, CH2O] complexes

Abstract: Bowen et U Z . ' .~ have proposed that H-bonded complexes are CH3=CHC%+ + OH2 m/z 41 E+ 0 1 + CH3CH20CH2 2 4 Scheme 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Over 100 papers have described the spectroscopic properties, reaction mechanisms and kinetics, ,,,,,,,,,,,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 100 papers have described the spectroscopic properties, reaction mechanisms and kinetics, ,,,,,,,,,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…Over 100 papers have described the spectroscopic properties, reaction mechanisms and k i n e t i c s , 3 , 6 , 8 , 9 , 1 5 , 2 1 , 2 4 , 2 5 , 2 9 , 3 0 , 3 7 , 3 8 , 4 2 , 4 6 -8 7 thermochemistry, 10,17,18,45,47,50,59,[78][79][80]83,[88][89][90][91][92][93][94][95][96][97][98][99] and ab initio calculations 13,22,61,89,93,94,96,97, of the hydroxymethyl (CH 2 OH) radical and cation. These studies were motivated by the important roles that CH 2 OH and its isomer, CH 3 O, play in the combustion of hydrocarbon fuels, atmospheric pollution chemistry, surface science, and interstellar chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…indicated that significant amounts of 13 C-label exchange occurs during ethylene elimination from labeled analogues of 1 9 and 7 8b. However, later labeling experiments on 1 11 and 7 10 and ICR experiments on mixtures of [ 13 CH 2 OH] + and CH 2 CH 2 have failed to observe significant 13 C-label exchange. , …”
Section: Discussionmentioning
confidence: 99%